2013
DOI: 10.1007/s10900-013-9656-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Sleep Quality Among Operating Engineers

Abstract: Blue collar workers generally report high job stress and are exposed to loud noises at work and engage in many of the health behavioral factors, all of which have been associated with poor sleep quality. However, sleep quality of blue collar workers has not been studied extensively, and no studies have focused Operating Engineers (heavy equipment operators) among whom daytime fatigue would place them at high risk for accidents. Therefore, the purpose of this study was to determine variables associated with sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Additionally, the majority of participants in our study were non-smokers and were physically active and within the recommended range for their ideal body weights [26]. Our findings that alcohol consumption increases the risk of poor sleep quality concur with previous reports [8]. In this study, we did not assess quantity of alcohol consumed per day; however, others have reported sleep quality is compromised with increased alcohol consumption [27].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, the majority of participants in our study were non-smokers and were physically active and within the recommended range for their ideal body weights [26]. Our findings that alcohol consumption increases the risk of poor sleep quality concur with previous reports [8]. In this study, we did not assess quantity of alcohol consumed per day; however, others have reported sleep quality is compromised with increased alcohol consumption [27].…”
Section: Discussionsupporting
confidence: 88%
“…Sleep quality is influenced by an array of factors ranging from demographic characteristics, to personal life style choices to type of work and condition of work environment [8]. Advanced age, unmarried status, smoking habit and alcohol consumption have been reported to compromise quality of sleep [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Newly hired workers at one of three cotton mills close to Istanbul, Turkey. Upper-Middle-Income ( Bakirci et al, 2007 ) Longitudinal Occupational class Asthma Blue-collar women vs. other women Compared with female administrators, managers, and clerical workers, the risk of asthma was increased among all blue-collar women (RR = 1.4, 95% CI 1.2–1.6), female woodworkers (RR = 1.5, 95% CI 1.2–1.7), and other blue-collar women (RR = 1.4, 95% CI 1.2–1.6). All residents of Finland employed in wood-processing industries.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on musculoskeletal disorders consistently showed increased risk for pain and work-related injuries in blue-collar women as compared with men ( Chin et al, 2012 , Carlsson and Karlsson, 1970 , Centre for Social Development et al, 2018 , Chenet et al, 1998 , Case and Paxson, 2005 , Catalano and Bruckner, 2006 , Chin et al, 2012 , Cantley et al, 2016 ). Similarly, blue-collar women exhibited inferior respiratory health compared with blue-collar men based on results from pulmonary function tests and airway responsiveness ( Choi et al, 2013 , Chin et al, 2013 , Cho and Lee, 2012 , Christensen et al, 2008 ). Comparisons of smoking frequency in male and female blue-collar workers, however, yielded inconsistent findings ( Cocco et al, 1999 , Cohidon et al, 2009 , Colt et al, 2011 , Cleland et al, 2011 , Clougherty et al, 2010 , Clougherty et al, 2011 , Cobankara et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%